Fraud Prevention Strategy at PT. PLN (Persero) Lhokseumawe Customer Service Unit - Yandri Doni; Rahima Br Purba (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research describes the implementation of fraud prevention strategies through internal control at PT. PLN (Persero) Lhokseumawe Customer Service Implementation Unit, with a focus on anti-bribery management system programs. The methods used include Gap Analysis to measure readiness to implement an anti-bribery management system as well as SWOT analysis combined with Strategic Factor Analysis to formulate implementation strategies in the short, medium and long term. The research results show that although PT. PLN (Persero) Lhokseumawe Customer Service Implementation Unit is ready to implement an anti-bribery management system, there is still a need for further development. Some of the main findings are that not all employees have received training regarding the anti-bribery management system and there has been no risk assessment of bribery. To overcome this, the research recommends several implementation strategies, namely Anti-Bribery Management System Training, Anti-Gratification Socialization, Bribery Risk Assessment, Activity Budgeting and Policy/Guideline Making. This strategy is expected to help PT. PLN (Persero) Lhokseumawe Customer Service Implementation Unit in strengthening good governance and reducing the risk of fraud through implementing an effective and sustainable anti-bribery management system